Transition of children from kindergarten to elementary school – experiences of preschool teachers from Bosnia and Herzegovina - Camović, Dženeta (Sodobna pedagogika, 2023)
Starting school is deemed a very challenging period of transition for children, parents, educators and teachers. Their active support and mutual cooperation are thus considered crucial for positive outcomes. This paper analyses the transition process of children from kindergarten to elementary school from the perspective of preschool educators in Bosnia and Herzegovina (BiH). Qualitative research was carried out through semistructured interviews with 18 preschool teachers, whose experiences of working with children contributed to understanding the process of transitioning from kindergarten to elementary school alongside the existing challenges. The research results indicate the use of the least efficient transition activities and the absence of collaboration and the sharing of information between kindergartens and schools, and they also highlight the needs of teachers regarding educational support and professional cooperation with elementary school teachers. Accordingly, the paper gives recommendations for the improvement and sustainability of the system of transitioning children from kindergarten to elementary school.
Keywords: education; elementary school; kindergarten; osnovna šola; pedagogika; pedagogy; transition; vrtec; vzgoja in izobraževanje